Metode Penafsiran Kontemporer Abid Al-Jabiri - Aulan Niam (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Abid Al-Jabiri is a character who was born in the middle of the 20th century in Morocco, a country that develops cultures of modernity. This certainly makes it a historical fact that Abid Al-Jabiri is a thinker who lives in the midst of a family that is fanatical about modernity. Departing from this fact, Abid Al-Jabiri became a person who knew deeply about how modernity developed. In his journey Abid Al-Jabiri received a lot of knowledge and wrote many phenomenal works. One of the sciences he studied was Tafsir Al-Qur'an, in which he produced a work which later became the subject of discussion by many researchers. This paper seeks to provide an overview of what Abid Al-Jabi's thoughts related to methods and practices related to observations in the Qur'an. The study used library research methods, then analyzed using descriptive-analytical models. From this model, a result is found that Abid Al-Jabiri gives an idea that in an effort to limit the Qur'an it cannot be separated from the historical aspects of the verses of the Qur'an. This is based on the fact that the verses of the Qur'an were not revealed to the Arabs regardless of the customs and culture that developed at that time. But besides all that, the textual side of the verse must be peeled first so that the information contained in the verse is conveyed in full. In this case, A Al-Jabiri expressed the idea that the bidding of the Qur'an must also consider the historical side of the verses of the Qur'an.